If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -6)(x + -6) = (x * x) + -396 Reorder the terms: (-6 + x)(x + -6) = (x * x) + -396 Reorder the terms: (-6 + x)(-6 + x) = (x * x) + -396 Multiply (-6 + x) * (-6 + x) (-6(-6 + x) + x(-6 + x)) = (x * x) + -396 ((-6 * -6 + x * -6) + x(-6 + x)) = (x * x) + -396 ((36 + -6x) + x(-6 + x)) = (x * x) + -396 (36 + -6x + (-6 * x + x * x)) = (x * x) + -396 (36 + -6x + (-6x + x2)) = (x * x) + -396 Combine like terms: -6x + -6x = -12x (36 + -12x + x2) = (x * x) + -396 Multiply x * x 36 + -12x + x2 = (x2) + -396 36 + -12x + x2 = x2 + -396 Reorder the terms: 36 + -12x + x2 = -396 + x2 Add '-1x2' to each side of the equation. 36 + -12x + x2 + -1x2 = -396 + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 36 + -12x + 0 = -396 + x2 + -1x2 36 + -12x = -396 + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 36 + -12x = -396 + 0 36 + -12x = -396 Solving 36 + -12x = -396 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + -12x = -396 + -36 Combine like terms: 36 + -36 = 0 0 + -12x = -396 + -36 -12x = -396 + -36 Combine like terms: -396 + -36 = -432 -12x = -432 Divide each side by '-12'. x = 36 Simplifying x = 36
| 45=2y | | 5x+43-2(x+7)=88-2x | | 0.16(y-2)+0.12y=0.20y-0.7 | | x^2-17X+3=0 | | 5x+43-2(x-7)=88-2x | | 8x^4+10x^3-14x^2-4x=0 | | 6x-3x=4x-1 | | y=4xn | | 2x^2-196-70x=0 | | 2y=.5x+6 | | x^3-klnx=0 | | x^3-klx=0 | | 2x-12=5x-43 | | 8x-5=2x-4.5 | | y=4x^2(5x-8) | | -8x^2+35x+-38=0 | | 1x+7=x+14 | | 22y=8y-98 | | 18x=150 | | 5y-9y=-14(-14) | | 8-x=4-.5x | | 12x+6=2x+26 | | 4x+50=13x-59 | | 0.50x+0.45(70)=34.5 | | 20y-20+20y=8y-100 | | 24x+7=30x-4 | | 3n+n-5+6= | | 3(1-2x)-5(3x)-6(3x-4)=83 | | 4+9=5 | | 28y=32y+2 | | 32+6x=12-8.5 | | -5a+12+7a=2a-4a |